Dynamics of the ionic liquid 1-butyl-3-methylimidazolium bis(trifluoromethylsulphonyl)imide studied by nuclear magnetic resonance dispersion and diffusion. Issue 3 (1st December 2014) - Ordikhani Seyedlar, Amin; Stapf, Siegfried; Mattea, Carlos
Abstract : NMR was used to study the dynamics of the ionic liquid Bmim-Tf2N in the supercooled regime. Rotation and translation molecular dynamics exhibit a transition at T c ∼1.26 T g . Abstract : The dynamics of the imidazolium based room temperature ionic liquid Bmim Tf2N was investigated by means of nuclear magnetic resonance relaxation dispersion (NMRD) and nuclear magnetic resonance pulsed field gradient (NMR-PFG) diffusion experiments on the bulk liquid in a wide range of temperatures. Relaxation and diffusion properties were determined for anions and cations individually, giving evidence of heterogeneities in the dynamics of the ionic liquid. The relevant NMR relaxation mechanisms are the inter- and intramolecular dipolar interactions between the molecular ions reflecting the molecular translational and rotational diffusion. Rotational and translational correlation times could be obtained and showed different dependences on temperature. The experimental diffusion values follow the Vogel–Fulcher–Tammann (VFT) relation above a transition temperature T c ∼ 1.26 T g, below which a deviation was observed. Differential scanning calorimetry experiments show a transition at the same temperature.